American observers in the Soviet Union : 1917-1933. - Gatewood, James Dewey, 1940- (My University, 1968)
Contents include: Americans and the Russian Revolution; Americans, the Russian front, and allied intervention; American observers and the Soviet political system; Americans comment on Soviet economic conditions; and observations on the Russian people and Soviet society.
266 leaves ; 29 cm.
Keywords: Soviet Union --Foreign relations --United States.